Preparation and characterization of high-performance wood polymer nanocomposites using multi-walled carbon nanotubes - Kaymakci, Alperen; Ayrilmis, Nadir; Gulec, Turker; Tufan, Mursit (SAGE Publications, 2016)
Effect of industrial grade multi-walled carbon nanotubes on mechanical, decay, and thermal properties of wood polymer nanocomposites was investigated. To meet this objective, pine wood flour, polypropylene with and without coupling agent (maleic anhydride grafted polypropylene), and multi-walled carbon nanotube (0, 1, 3, 5 wt%) were compounded in a twin screw co-rotating extruder. The mass ratio of the wood flour to polypropylene was 50/50 (w/w) in all compounds. Test specimens were produced using injection molding machine from the pellets. The flexural and tensile properties, biological durability, and thermal analysis (thermogravimetric analysis and differential scanning calorimetry) of the nanocomposites were investigated. The flexural and tensile properties of the wood polymer nanocomposites increased with increasing content of the industrial grade multi-walled carbon nanotubes (from 1 to 5 wt%) and maleic anhydride grafted polypropylene (3 wt%). The mass loss rates of the wood polymer nanocomposites decreased with increasing amounts of the maleic anhydride grafted polypropylene and industrial grade multi-walled carbon nanotube. The differential scanning calorimetry analysis showed that the melt crystallization enthalpies of the wood polymer nanocomposites increased with increasing amount of the industrial grade multi-walled carbon nanotubes. The increase in the Tc indicated that the industrial grade multi-walled carbon nanotubes were the efficient nucleating agent for the wood polymer nanocomposites.
Keywords: 13. Climate action; 7. Clean energy